(untitled) (Research, Society and Development, 2020)
According to current evidence, an increasing number of patients seeking the public health system for sexually transmitted infections (STIs) are in the age group associated with adolescence, a period commonly related to unplanned pregnancy. This worrying situation is associated with little knowledge about sex education by young people, due to the lack of information and guidance. Therefore, this theme was chosen with the objective of promoting the sexual education of young people and adolescents, with the aim of preventing STIs and pregnancy in this population as a result. Faced with this problem, a descriptive epidemiological study with quantitative analysis regarding the knowledge of adolescents related to sexual health, collected through questionnaires applied before and after a round of conversation held with elementary school students, in the eighth and ninth years, of a public school in the state of Pará. From this, an analysis of the results identified an average increase of 24% of correct answers in the eighth grade class and 14% in the ninth grade class. It is inferred, therefore, that the practice of social intervention in the following study resulted in an increase in students’ knowledge about the subjects covered based on the applied tests. In view of this, it is expected that from this approach there will be a positive impact on the lives of these students and their community.